2019
DOI: 10.1111/jog.13925
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of antibody negative and untreated subclinical hypothyroidism

Abstract: Aim Subclinical hypothyroidism is thought to be associated with adverse pregnancy outcomes but the data is conflicting and generally depends on antibody positivity and treatment. We evaluated the pregnancy outcomes in Turkish population with untreated, antibody negative subclinical hypothyroidism for the first time. Methods We searched for 30 015 patients between January 2016 and May 2017 retrospectively. Finally, a total of 930 pregnant women with untreated, antibody negative subclinical hypothyroidism and 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In addition to SCH, multiple factors including hormonal disorders, imbalances of angiogenic factors, and placental hypoxia also contribute to high blood pressure (24). In women with SCH, the mechanism for HDP may be based on decreased nitric oxide secretion and impairment of vasodilation in endothelial tissues (25). Hypercoagulability, increments in blood viscosity, and lipid abnormalities in patients with SCH potentially increase the risk for atherosclerosis; the increase of blood pressure in SCH may be related to these factors (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SCH, multiple factors including hormonal disorders, imbalances of angiogenic factors, and placental hypoxia also contribute to high blood pressure (24). In women with SCH, the mechanism for HDP may be based on decreased nitric oxide secretion and impairment of vasodilation in endothelial tissues (25). Hypercoagulability, increments in blood viscosity, and lipid abnormalities in patients with SCH potentially increase the risk for atherosclerosis; the increase of blood pressure in SCH may be related to these factors (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that there is no sufficient evidence whether a universal screening should be recommended for TSH concentrations before pregnancy, but they have made an exception for women planning assisted reproduction techniques and those determined positive ATA. However, a recent large-scaled retrospective cohort study showed that the worse pregnancy outcomes were determined in subclinical hypothyroidism compared to euthyroid pregnancies even in antibody negativity [33].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, there were no significant differences in the incidence of GDM, PROM, HDP, preterm birth, fetal distress, low birth weight, fetal macrosomia, and SGA between the hypertension, but does not increase the incidence of GDM, intrahepatic cholestasis in pregnancy, PROM, fetal growth restriction, and preterm delivery. A retrospective study (8) revealed that thyroid autoantibody-negative SCH increased the risk of miscarriage, abnormal GS tolerance, HDP, and placenta previa. A meta-analysis( 23) involving SCH and GDM showed that SCH with positive antithyroid autoantibodies in pregnancy is associated with an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that SCH with TAI increases the risk of miscarriage, preterm birth, and GDM (6,7). Nevertheless, a previous retrospective study (8) involving 3,015 pregnant women revealed that untreated thyroid autoantibody-negative SCH increased the risk of miscarriage, abnormal blood glucose (GS) tolerance, placenta previa, and placental abnormality. A meta-analysis (9) confirmed that SCH is a risk factor for miscarriage and found that early treatment can reduce the rate of miscarriage.…”
Section: Introductionmentioning
confidence: 99%